Implementation of Sustainable Finance Regulation for Financial Institutions in Indonesia - Hayu S Prabowo (Jurnal Ilmu Manajemen dan Ekonomika, 2023)
The interaction between people and the environment are very vital because functioning ecosystem services are important resources for people. Economy is a subsystem of human society, which is also a subsystem of life on earth and its ecosystem. The issue of environmental change has shifted from a peripheral concern of scientists and environmentalists to being a central issue in global policymaking. To ensure global long-term financial stability and economic development, financial institutions need to significantly change their performance to promote more responsible and sustainable business practices. The Financial Services Authority of Indonesia has unveiled a roadmap, which sets forth the end goal of sustainable finance in Indonesia by the financial services industry and determines the benchmark for improvements in sustainable finance. This paper explains the reasoning and implementation of sustainable financing policies under the term of Environment, Social, and Governance concepts. This paper explains the complementarities of the Islamic worldview and sustainable financing policies by opening up the topic of the scientific nature of heterodox Islamic economics in particular. The term sustainable financing conveys the fact that society and economics, finance, environment, governance, polity, institutions, etc. cannot be independent of a unique and common set of moral and ethical values. The ESG concept is completely in line with the Maslahah concept under shariah law. It embeds moral and ethical values in the body of heterodox Islamic economic thought aligned with the shariah ruling.